Perceptions of teachers and students on the new social studies in Malabang National High School - Barazar, Sitty Mona Tamse 1950- (1978)
This study aimed to determine the perceptions of social studies teachers and fourth year students on social studies instruction in Malabang National High School in relation to other academic subjects. The data were obtained primarily through questionnaires administered to 104 fourth year students and three teachers of Malabang National High School. It was concluded that the students perceive their Social Studies lessons as wholesome and beneficial, and provide them the necessary background knowledge for future use. The teachers share the same perception as well. They also believe that the methods of the new social studies are also more relevant and acceptable to their students, which was supported by the concurrence of the response of the students. Thus, teachers and students of the said high school showed their appreciation of social studies as a course worthy of teaching and learning.